Anti-fungal activity of irradiated chitosan against Exobasidium vexans Massee - Le Ha, Pham Thi; Thuy, Tran Thi; Hai, Le; Hien, Nguyen Quoc (Academia Journal of Biology, 2015)
Anti-fungal activity of irradiated chitosan against Exobasidium vexans Massee